An Experiment with the Warp-weighted Loom and Heavy Loom Weights. The Case of the Giant Refractory Ceramic “Doughnuts” from North Piedmont, Italy - Lorena Ariis (EXARC, 2020)
Heavy, doughnut-shaped, loom weights made of refractory clay are often found in excavations of Roman and Late Roman settlements in North Piedmont. Unfortunately, they are not found in situ with a weaving loom. We have interpreted them as having been specifically designed for use on a warp weighted loom with a lower mobile beam which is weighed down by a few heavy loom weights. This weaving loom might have been a local model which appeared before the Medieval double beam weaving loom. Our experiment consists of reproducing the weaving loom and weaving a simple tabby weave made from wool commonly used in the area during the Roman Period.